Factors Influencing Patient Satisfaction in the KIA Unit - Priyanti, Sari; Safitri, Citra Adityarini; Syalfina, Agustin Dwi; Sulistyawati, Wiwit; Irawati, Dian; Sukarsih, Anik (Jurnal Kebidanan Midwiferia, 2025)
The quality of midwifery services has three main components: patient care, technical quality, and customer quality. Service quality refers to non-healthcare aspects of care and reﬂects the patient's experience with the healthcare system, including the relationship between the client and the provider and the standard of facilities. Service satisfaction is now a usual way to check how good healthcare is. This study looked at how midwifery services at the Jeruk Community Health Center in Pacitan Regency affected how satisfied patients were. The study used a cross-sectional method to look at the data. It took place at the Jeruk Community Health Center in Pacitan Regency in January 2024. A total of 125 people got a 3-month injection. From these, 54 were chosen as participants through simple random sampling. Information was collected using a questionnaire. The data was analyzed using a chi-square test. The results showed Midwifery services on patient satisfaction are an indicator of the Community Health Center's success in providing services. Therefore, the performance of both health workers and other supporting staﬀ needs to be maintained and further improved to improve health services at the Jeruk Community Health Center in Pacitan Regency.